Remunerating conservation: The Faustmann-Hartmann approach and its limits - Ulrich Hampicke (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 1998)
The method introduced by Faustmmm and extended by Hartman is used for calculating present values of forestry assetts under various conditions and for determining the optimal rotation. The approach is not stochastic and very simple. The forest benefit contemplated additional to timber is the conservation of biodiversity. It is well established that the redevelopment of old forests including decay stages is by far the most efficient measure to enhance the survival chances of endangered species. For simplicity, it is assumed that the forest 's value increases linearly with age. For this case, it is not only easy to calculate the payments necessary to incite the forest owner to delay the time of harvest, hut also to give a simple condition for it becoming profitable to abstain from wood harvesting altogether. A numerical simulation is carried out using data from typical Central European beech forests (Fagus sylvatica). Payments and present values capable of persuading owners never to harvest are very high, as compared to conventional income from forestry. Society has to decide on the basis 01 its value judgements whether or not such payments are warranted important problems include liquidity and risk, the choice of an interest rate, forest management costs and the necessity of spatial planning. It is concluded that without financial incentives the perspectives for conservation in forestry are precarious, at least in Germany. On the other hand, a fair remuneration is only one measure and cannot alone salve the problems. It has to be integrated info a bundle of appropriate planning instruments.
Keywords: 330